Uma análise da atuação do revendedor da venda direta no setor de higiene pessoal, perfumaria e cosméticos aplicada no contexto brasileiro - Schunck, Josiane Garcelli (2016)
The concept of direct selling is defined as a way of marketing products through personal contact without fixed business location (Peterson & Wotruba, 1996). In the industry of personal care, perfumery and cosmetics direct sales channel represents 25% of total revenue in Brazil, but there are companies that operate with several of them and coexisting distribution models that can go from department stores, drugstore and e-commerce. The representativeness of some of these sales channels begins to grow and, considering the direct selling model, the role of the independent sales representative is fundamental so that Direct Sales companies can access the consumer and remain competitive. DS companies depend on the representative actions, being the reason they have developed initiatives that aim to improve their performance. In this way, studying the role of the sales representative can bring contributions to the literature once in previous studies, although they were done with representatives, it could not observed this new context of the industry. The subject of study of this work was the direct sales representatives who commercialize several brands of cosmetics produced by different direct sales companies. The objective of this research was to understand if there is a causal relationship between the representative satisfaction, the activities she or he does during the sales process such as sales management, channel management and the effort she or he has to. It also aimed, once this effort is identified, to understand the relationship of it with the sales performance and outcome representative. A survey was sent to a group of representatives in Brazil and 1,243 responses were obtained. Based on these responses, Exploratory (AFE) and Confirmatory (AFC) Factorial Analysis and a Structural Equations Model (MEE) was developed to illustrate this relationship among variables. The Expectancy Theory was used to understand the relationship between Effort, Performance and Rewards from the perspective of the representative. The results showed that channel management is the factor that most influences the representative effort, it has a strong relationship with its performance, and outcome, confirming the Expectancy Theory applies for the direct sales business model. The analysis also allowed us to conclude that channel management and sales management are important points, since the representative, who acts as a channel him or herself, is not yet prepared or considered. Direct selling companies need to develop their independent sales representatives as marketing channel, to generate competitiveness in a multichannel environment direct sale is inserted.